The Short Life of Free Georgia : Class and Slavery in the Colonial South - McIlvenna, Noeleen, 1963- (Book collections on Project MUSE., 2015)
This text tells the foundation story of Georgia, chartered in 1732 to be a charity colony for poor white Europeans. Southern history is most often viewed through the lens of race. But the philanthropist Trustees banned slavery for the first 20 years of settlement, so the political perspective of the poor settlers reflected the rigid hierarchy of social class as English people of the time understood it.